A multi-lander New Frontiers mission concept study for Enceladus: SILENUS - Nathan, Erica; Balachandran, Katiyayni; Cappuccio, Paolo; Di, Julia; Doerksen, Kelsey; Gloder, Alessia; Li, Monica; Massarweh, Lotfi; Peev, Thomas; Santra, Shreya; Rovira-Navarro, Marc; Limonchik, Dan (Frontiers in Astronomy and Space Sciences, 2022)
Enceladus, with its subsurface ocean, is amongst the top priority targets in the search for life beyond Earth. Following on discoveries from the Cassini mission that Enceladus possesses a global subsurface ocean containing salt and organic compounds, there are many unconstrained properties of the ocean and ice shell that must be investigated to further assess the habitability of Enceladus and begin the search for biosignatures on Enceladus. In this paper, we present a concept study for a New Frontiers class multi-lander and orbiter mission to Enceladus that investigates if there is or ever was a habitable environment on Enceladus. The mission architecture includes an orbiter for detailed chemical analysis of material erupted from Enceladus’ plumes and four impact landers for geophysical measurements. As part of our mission concept study, we explore key trades for orbital and surface science, as well as assess the scientific potential and hazards of candidate landing sites on Enceladus. The novelty of our mission architecture and consideration of both orbital and surface science elements makes this work directly relevant to a broad range of potential future mission architectures under consideration, such as those identified in the 2023-2032 Planetary Science and Astrobiology Decadal Survey.